Language policy and planning in the context of language law and their role in preserving the status of the Kurdish language - Shalaw Saleh Hamagharib; Mizgin Abdulrahman Ahmad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
In today's world, language policy, planning, and law are current issues of interest to researchers and linguists. These aspects can have a positive or negative impact on languages and are involved in the preservation or destruction of one or more languages. That is why they are of great importance in linguistic research and the formulation of state policies. This paper summarizes a doctoral thesis entitled (The Position of Kurdish Language in the Context of Language Policy). Here he tries to explain each area of language policy and law and present their relationships and complementarities. At the same time, it should highlight their role in preserving/destroying and enhancing/lowering the status and dignity of the Kurdish language and analyze the developments and consequences of the implementation and non-implementation of the language law. In other words, the study focuses on an important and sensitive issue of this stage of the Kurdish language, which is its position and aims to explain the impact of the language law as a constitutional stage and complement language policy and plan. So that it can become a viewpoint for the right direction for the future of the Kurdish language.